2007
DOI: 10.1097/01.aog.0000264552.85436.a1
|View full text |Cite
|
Sign up to set email alerts
|

Placental Growth Factor and Soluble FMS-Like Tyrosine Kinase-1 in Early-Onset and Late-Onset Preeclampsia

Abstract: Both early- and late-onset preeclampsia are associated with altered plasma levels of sFlt1 and PlGF. The alterations are more pronounced in early-onset rather than in late-onset disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
61
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(74 citation statements)
references
References 26 publications
12
61
0
1
Order By: Relevance
“…It is thought that these defects impair the development of the fetal-maternal vasculature and result in placental ischemia and hypoxia, which contribute to the pathogenesis of preeclampsia (1)(2)(3). Consistent with this model, expression of the antiangiogenic protein soluble Flt-1 (Fms-like tyrosine kinase-1) (sFlt-1) 3 is elevated, whereas expression of the proangiogenic vascular endothelial growth factor (VEGF) and placental growth factor (PGF) is decreased in preeclampsia (4,5). Systematic surveys of pregnant women have further revealed that the ratio between the circulating levels of sFlt-1 and PGF increases significantly prior to the onset of preeclampsia (6,7).…”
mentioning
confidence: 89%
“…It is thought that these defects impair the development of the fetal-maternal vasculature and result in placental ischemia and hypoxia, which contribute to the pathogenesis of preeclampsia (1)(2)(3). Consistent with this model, expression of the antiangiogenic protein soluble Flt-1 (Fms-like tyrosine kinase-1) (sFlt-1) 3 is elevated, whereas expression of the proangiogenic vascular endothelial growth factor (VEGF) and placental growth factor (PGF) is decreased in preeclampsia (4,5). Systematic surveys of pregnant women have further revealed that the ratio between the circulating levels of sFlt-1 and PGF increases significantly prior to the onset of preeclampsia (6,7).…”
mentioning
confidence: 89%
“…A look into studies exploring early-and lateonset pre-eclampsia also yields differing results. There are many studies that assert that maternal serum sFlt-1 in both early-and late-onset pre-eclampsia is higher than in the control group [19,28,32] but also some that report no difference, some that state that sEng is higher than in the control group [19,28,33,34], that PIGF is lower in the pre-eclampsia group [33], or higher [19] or no different than in the control group [28]. In this study sEng levels in the umbilical cord serum were found to be significantly higher in the early-onset pre-eclampsia group than the control group.…”
Section: Angiogenic and Anti-angiogenic Factors In Early-and Late-onsmentioning
confidence: 99%
“…The present study revealed no significant difference between early-and late-onset pre-eclampsia groups in any of the factor levels in either the maternal or the umbilical cord serum. Most of the studies in this area indicate that particularly in earlyonset pre-eclampsia, the angiogenic factors PIGF and VEGF show a more pronounced decrease while the anti-angiogenic factors sFlt-1 and sEng exhibit a more distinct increase [33,35]. On the other hand, it has also been brought forth that increased sFlt-1 appears to be potentially responsible for more severe cases of pre-eclampsia as opposed to milder cases [32].…”
Section: Angiogenic and Anti-angiogenic Factors In Early-and Late-onsmentioning
confidence: 99%
“…Unlike sflt-1, VEGF and PlGF alternations can be found at the end of the first trimester of pregnancy complicated with PE. VEGF has also been confirmed to be associated with origin of the disease [22,23]. In a study of mice, a half cut off of VEGF expression could result in proteinuria and glomerular endothelial injury.…”
Section: Angiogenic Factorsmentioning
confidence: 93%
“…It suggested that excess circulating sflt-1 may contribute to the pathology of PE [1,3,21]. In contrast, VEGF and PlGF have been reported decreased in PE patients [22]. As sflt-1, alternations of levels of VEGF and PlGF are shown prior the onset of the symptoms.…”
Section: Angiogenic Factorsmentioning
confidence: 99%